A long, winding trajectory of suffering with no definite start and uncertain future prospects – narratives of individuals recently diagnosed with fibromyalgia - Anne Marit Mengshoel (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Purpose Fibromyalgia is a contested illness with unknown aetiology and poorly understood development. The present aim is to explore the pre-diagnostic illness trajectory narrated by individuals recently diagnosed with fibromyalgia (FM). Methods Individual interviews about the course of the illness were conducted with seven women and three men (age from early 20s to 50s) who had recently been diagnosed with FM. A narrative analysis of what the interviewees told and how the stories were narrated was conducted. Results The findings are expressed by three storylines. “Strenuous life and alerted body preluding illness” displays a difficult, unsupported life and bodily sensitivity to stimuli. “Recurrent pains unfolding to become a lasting and complex illness” describes individuals pushing themselves to meet social obligations until they come to a full stop. “Diagnosed but still uncertain presence and future” portrays satisfaction with finally being diagnosed with FM and being supported by others, but still there are no solutions as to do about it. Conclusions The three storylines portray a long, winding trajectory of suffering starting before the onset of illness, and unfolding illness gradually becoming persistent and overwhelming. Finally, a diagnosis of FM is arrived at, but how the situation will evolve is uncertain.